DENSITY FUNCTIONAL THEORY APPROACH IN INVESTIGATING STRUCTURAL AND ELECTRONIC PROPERTIES OF BISMUTH-BASED PHOTOCATALYSTS - Huyen Nhung, Nguyen; Phan Thuy Linh, Tran (HNUE Journal of Science: Journal of Natural Sciences, 2025)
Utilizing Density Functional Theory (DFT) as the computational method, we aimed to gain insights into the structural and electronic characteristics of Bi-based photocatalysts, particularly bismuth tungstate and bismuth molybdate. Both materials exhibit an orthorhombic structure and belong to the space group Pca21 under certain conditions. The exchange-correlation functional used throughout the study was the Perdew-Burke-Ernzerhof (PBE) functional within the generalized gradient approximation (GGA), enabling detailed analyses of their crystal structure, electronic band structure, density of states, and charge density. The electronic properties of both photocatalysts exhibit similar features as expected from the similarities in crystal structure. Notably, bismuth molybdate has a narrower band gap than bismuth tungstate, attributed to the atomic size difference between molybdenum and tungsten. The results confirm their semiconductor nature, highlighting their potential for sustainable-energy photocatalytic applications.